Fourier Transform Infrared Spectroscopy and Gravimetric Analysis of Protein Denaturation in Egg Albumen Treated with Colocasia esculenta L. Schott (Taro) Leaf Extract - Castillo, Ronald Andrei; Dilag, Ariel Ziv; Mira, Iyanna Francine; Panganiban, Sebastian; Gigantone, Marcelino; Adan, Angelo Albert; Alafriz, Thyrene Chelsea; Bautista, Yoshabel Chelsea; Ostria, James Kurt; Vigilia, Carmela Felicia (Journal of Interdisciplinary Perspectives, 2025)
One of the leading factors contributing to the development of neurodegenerative disorders like Alzheimer's and Parkinson's disease is protein misfolding. When this occurs, these proteins lose their proper form, thereby leading to dysfunction and aggregation. Limited remedies that focus on symptomatic relief have been developed, thereby leading to plant-derived compounds gaining attention as their potential to stabilize proteins. The study aims to determine taro leaf extract's effect combined with egg albumen on protein structures observed through infrared spectroscopy, evaluating protein structural change and mass measuring for protein denaturation. Researchers compared four concentrations (12.5, 25, 50, and 100%) to diclofenac sodium and distilled water, with all groups containing egg albumen. Only 100% concentration and control groups were analyzed using FT-IR spectra, revealing hydrogen bonding interactions and structural differences by distinct shifts in Amide I bands. Through deconvolution, 100% concentration showed the highest α-helix content, presence of β-sheet, and no random coil signals, revealing preservation of native secondary structure and protein stability in opposite to negative control. The gravimetric analysis revealed increased mass in higher extract concentrations. A one-way ANOVA for gravimetric analysis yielded a p-value of 7.11 × 10^ (-5), indicating significance between groups. Tukey's HSD post hoc test showed significance between 100% and the concentrations (12, 25, and 50%) with pvalues of 0.013, 0.016, and 0.017, indicating distinct aggregation caused by 100% compared to the lower concentrations. Moreover, no significant differences were compared to controls with p-values of 0.149 and 0.584, suggesting aggregation and coagulative activity. Findings suggest that the extract exhibited secondary protein structural stabilizing effects on α-helix and β-sheet structures, potentially preventing misfolding despite presence of aggregation. However, further investigation is needed to evaluate its role as a coagulative agent and to understand its dosage-dependent behavior, offering valuable insights for future therapeutic approaches to protein misfolding-related conditions.